2021
DOI: 10.1097/md.0000000000027653
|View full text |Cite
|
Sign up to set email alerts
|

The effect and safety of ropinirole in the treatment of Parkinson disease

Abstract: Background:It is necessary to conduct a meta-analysis of the clinical randomized controlled trials (RCTs) on ropinirole in the treatment of Parkinson disease (PD), to explore the effects and safety of ropinirole, and to provide a theoretical basis for clinically safe and rational drug use.Methods:RCTs on the effectiveness and safety of ropinirole in the treatment of PD were searched. We searched Dutch medical literature database, Pubmed, Cochrane Library, China National Knowledge Infrastructure, Wanfang Knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
(100 reference statements)
0
2
0
1
Order By: Relevance
“…Previous NMA (12) also showed that ropinirole did not improve the UPDRS II compared with placebo in early PD. Although other NMAs (8,(10)(11)(12) and meta-analyses (39) showed that ropinirole was associated with a significant improvement in the UPDRS-II compared with placebo, early PD and advanced PD were not analyzed separately, and ropinirole PR and ropinirole IR were not analyzed separately. Therefore, more research is needed to confirm the efficacy of ropinirole PR in early PD.…”
Section: Discussionmentioning
confidence: 99%
“…Previous NMA (12) also showed that ropinirole did not improve the UPDRS II compared with placebo in early PD. Although other NMAs (8,(10)(11)(12) and meta-analyses (39) showed that ropinirole was associated with a significant improvement in the UPDRS-II compared with placebo, early PD and advanced PD were not analyzed separately, and ropinirole PR and ropinirole IR were not analyzed separately. Therefore, more research is needed to confirm the efficacy of ropinirole PR in early PD.…”
Section: Discussionmentioning
confidence: 99%
“…Ropinirole primarily stimulates D2 and D3 receptors and has little affinity for D1, adrenergic and serotonergic receptors [ 125 ]. Ropinirole can be used as a monotherapy for early PD or in combination with levodopa for the management of advanced PD [ 126 ]. A randomized clinical study involving 161 early PD subjects found that ropinirole 24-hour sustained release and ropinirole immediate release showed similar efficiency in improving UPDRS motor score in early PD patients [ 127 ].…”
Section: Da Agonists Already Approved For Pdmentioning
confidence: 99%
“…Крім того, через можливе ураження клапанів серця агоністи дофаміну був практично виключений з медичної практики. Також нещодавне проведене дослідження іншого агоніста дофаміну ропініролу продемонструвало його ефективніть при ХП, зокрема на ранніх стадіях хвороби [22]. Обидва вище згадані препарати мають селективну активність щодо сайтів класу D2 (зокрема, щодо білківрецепторів D2 і D3) і незначну активність щодо сайтів класу D1.…”
Section: Introduction / вступunclassified